2019
DOI: 10.1186/s12879-019-4599-6
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies of diarrhea and drug susceptibility patterns of bacterial isolates among under-five year children in refugee camps in Gambella Region, Ethiopia: a case control study

Abstract: BackgroundDespite substantial global effort and updated clinical management guidelines, diarrhea continues to be among leading worldwide causes of morbidity and mortality in children. Infectious diarrhea, the most common form of diarrhea causes substantial morbidity and mortality among children in developing countries, and the muddled use of antibiotics needs caution due to potential problems of drug-resistance. The aim of this study is to identify etiologies of diarrhea and drug susceptibility patterns of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…There are chances that UNHCR will face a drop in funds. This will further worsen the situation for these displaced people including 37 million children living in these camps [5,6]. World has to act smartly in order to prevent another human crisis in coming months.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…There are chances that UNHCR will face a drop in funds. This will further worsen the situation for these displaced people including 37 million children living in these camps [5,6]. World has to act smartly in order to prevent another human crisis in coming months.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…World has to act smartly in order to prevent another human crisis in coming months. Periodic diarrhea, malaria and polio cases had been reported from these refugee settlements in the past [6]. It is high time for global community to act swiftly to save these lives.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…were detected in 28 (18.80%) stool samples. In the research conducted by Mekonnen, Mengistie, Sahilu, Kloos, & Mulat (2019), 10.50% shigella bacteria were found from a total of 134 samples examined. In another study, 7% were infected with Shigella bacteria (Zhu et al, 2016), and in Ghana, there were 5.60% positive Shigella from 347 samples examined (Ashie et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, there is evidence that microbes at one site can affect the host at other sites, and interesting discoveries on gut microbial community linked with the milieu of the brain, respiratory and urogenital tracts, heart and skin, resulting in that microbial community might be new approaches to health maintenance, disease prevention and even treatment (Reid et al, 2017 ). Diarrhea is related to an imbalance in the gut microbiota, such as the presence of specific pathogens like Clostridium (Mallina et al, 2018 ), Salmonella (Tadesse, 2014 ), and Escherichia (Chingwaru and Vidmar, 2017 ; Mekonnen et al, 2019 ). Given the potential resistance effects of some antibiotic therapies for bacterial diarrhea, studies have suggested that probiotics could be an effective strategies in combatting these diarrheal diseases (Szajewska et al, 2011 ; Hojsak et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%